PENGARUH RESPON KOGNITIF FOLLOWERS PADA KONTEN PROMOSI DI INSTAGRAM @transstudio.bandung TERHADAP MINAT BELI TIKET - Sudibyo, Rachmatya Pramesti Agisha Nimasratu; El Karimah, kismiyati; Mirawati, Ira (Universitas 17 Agustus 1945 Surabaya, 2025)
The development of information technology in the era of globalization has changed the order of people's lives, including in the field of marketing. Companies are now utilizing digital platforms, especially social media, to interact and influence consumers. One of the rapidly growing social media is Instagram, which is used by companies to promote their products or services. Trans Studio Bandung is an entertainment area in Bandung that actively uploads promotional content on Instagram social media accounts to attract visitors. This study aims to analyze the effect of promotional content published on the Instagram account @transstudio.bandung on the interest in buying tickets of its followers. Using cognitive response theory, which divides cognitive processes into thoughts about products, sources, and ad executions, this study examines how the audience's cognitive response to the content received can influence attitudes and purchase intention. This research examines whether audience engagement with Instagram content can increase interest in purchasing tickets. Using a quantitative approach, this study takes ticket purchase intention as the dependent variable and analyzes the influence of cognitive responses on purchase decisions. The results of this study are expected to provide a better understanding of the role of social media in marketing and the influence of promotional content on consumer behavior.